Genotype × Environment Interaction and Yield Stability Analysis in Hybrid Rice (Oryza sativa L.) By AMMI Biplot - Akter, Anowara; Hasan, M Jamil; Kulsum, MU; Rahman, MH; Paul, AK; Lipi, LF; Akter, Salma (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 79-86 to 83-90. Assessing the adaptability and stability of promising rice genotypes is one of the important steps for accurate evaluation. This study determined the genotype × environment interaction (GEI) and stability performance of 12 promising rice genotypes in four environments during 2009 Aman season. The experiment used randomized complete block design with three replications. Yield stability and adaptability of yield performance were analyzed by combined analysis and additive main effects and multiplicative interaction (AMMI) model. The environment, genotype main effects, and the GEI were all highly significant (P<0.001). The study indicated that the tested genotypes, such as BRRHA G1 (5.47 tha-1), G2 (5.68 tha-1), G3 (6.29 tha-1) and G4 (5.27 tha-1) had higher average yields, which indicated these genotypes adapted to favourable environments (E1 and E3). Whereas the environment, E3 could be regarded as a more stable site for high yielding hybrid rice improvement than the other locations. Based on AMMI biplot analysis, genotypes BRRI1A/BRRI827R (G1), IR58025A/BRRI10R (G2), BRRI 10A/BRRI 10R (G3) and BRRI hybrid dhan1 (G4) have higher average mean yields with high main (additive) effects and positive IPCA1 score, among them BRRI 10A/BRRI10R (G3) being the overall best. Locations E1 and E3 could be regarded as a good selection site for rice hybrid improvement due to stable yields. Bangladesh Rice j. 2015, 19(2): 83-90